Oswald Balzer versus Theodor Mommsen – polityczne emocje z historią w tle. Nowa ocean sporu - Słapek, Dariusz (Studia Europaea Gnesnensia, 2012)
There is a prominent tendency in the abundant literature concerning Th. Mommsen to portray him as an active, valued liberal politician of the second half of the 19th century. In this context, relatively little is said about his appeal to the Sudeten Germans of 1897 who faced the socalled Badenischen Sprachenverordnungen. The letter of the German scholar, published in the Viennese press, included many violently unjust accusations, especially against the Czechs. In the storm of polemics and discussions unleashed by the text, the voice of the Polish historian of law, Oswald Balzer, was probably the loudest. His open letter, defending the civilisational achievements of the Slavs, never received Mommsen’s response. Nonetheless, in the awareness of Poles and Czechs in particular the Berlin historian became their confirmed enemy. German science, making light of the event, puts it down to Mommsen’s unbridled political fervour, which made him speak out in public even in those matters of which he had little knowledge. It admits, however, that the episode with pure nationalism looming in the background is a certain flaw on Mommsen’s idealized image of an ever valid role-model of a liberal politician. The view is admissible, although one may be surprised at the implied ignorance of Mommsen’s especially with regard to the Sudeten Germans, to whom the language laws introduced by Count Badeni’s government were to apply, and which he knew well from his native Schleswig. As to the negligible knowledge Mommsen had of the Slavs, the views conveyed by Croatian Slavist V. Jagić may be convincing to some extent, although it is worth remembering that Mommsen (a person perfectly conversant with the nuances of world politics!) needed no profound academic knowledge to formulate general (remote from scientific inquiry) views about the Czechs. It is likely that when attacking Slavs, he drew upon the stereotypes which circulated at the time (he was not entirely independent in his opinions about Poles, remaining under the influence of M. Weber), supported by more readily definable personal views on the role of the Church and Catholicism, or the frontiers of the German state. Mommsen probably never formulated his convictions concerning Poles and the Polish issue of the turn of the 19th and 20th centuries in a consistent, logical statement. In the Polish press before 1897 he had not been treated as a declared enemy of Polishness and even his adversary, Balzer emphasised Mommsen’s former objectivity. It appears it was theLvov law historian who lacked objectivity. His disputatious character, apparently combined with the a fairly unpleasant memory of studies inBerlin (personal encounter with the demanding Mommsen) materialised in a polemic manifesto, in which, with a characteristic fluency, large dose of emotion and patriotic throes (although resorting to the standard historical argumentation of the time), the author drew a fairly unequivocal, anti-Polish image of Mommsen. This view persisted as long as 1918, although the admirers of Balzer’s views maintained it long after the death of both adversaries.